2004
DOI: 10.1177/0143831x04044831
|View full text |Cite
|
Sign up to set email alerts
|

Lean Production Assessed by Karasek’s Job Demand–Job Control Model

Abstract: Comments on the quality of working life (QWL) under lean production have varied from devastating criticism on the one hand, to eulogistic praise on the other. These contrasting positions can be related to researchers' opposing societal stances and resulting interpretations, which are reinforced by the methodologies used and the absence of an external framework to judge QWL. Using Karasek's job demand-job control model, the authors investigate a Dutch plant operating under a lean production (LP) regime in an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 32 publications
4
64
0
2
Order By: Relevance
“…In the local and district offices (the LPOs and DPOs), although the mechanisms did exist by which employees could play a significant role in both the creation and the development of operating procedures, little effective use was being made of them. We can thus take heed of Schouteten and Benders' (2004) caution that account should be taken of the extent to which employees are able to exercise a heightened degree of autonomy. In the more specialist operations undertaken in the national-level processing centres, on the other hand, the centres' managers retained a greater degree of control over processes and were able to use this to encourage greater Survey (2011) shows working as a member of a team to be the most positive aspect of work amongst those surveyed in HMRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the local and district offices (the LPOs and DPOs), although the mechanisms did exist by which employees could play a significant role in both the creation and the development of operating procedures, little effective use was being made of them. We can thus take heed of Schouteten and Benders' (2004) caution that account should be taken of the extent to which employees are able to exercise a heightened degree of autonomy. In the more specialist operations undertaken in the national-level processing centres, on the other hand, the centres' managers retained a greater degree of control over processes and were able to use this to encourage greater Survey (2011) shows working as a member of a team to be the most positive aspect of work amongst those surveyed in HMRC.…”
Section: Discussionmentioning
confidence: 99%
“…Schouteten and Benders (2004), for example, in their study of the Netherlands-based plant of a Taiwanese bicycle manufacturer, found that workers' involvement in continuous improvement activities accounted for only a small proportion of their working time. Their study resonates with the 'contradiction' identified by Conti and Warner (1993) in their examination of the nature of work in a number of Japanese manufacturing plants.…”
Section: Autonomy In Lean Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies are, however, finding that lean manufacturing has a mixture of positive and negative effects on working conditions and well-being (Anderson-Connolly et al, 2002;Conti, Angelis, Cooper, Faragher & Gill, 2006;Godard, 2001;Jackson & Mullarkey, 2000;Seppällä & Klemola, 2004). Indeed some have even demonstrated that employees in jobs with higher complexity experienced job improvements such as increased participation in decision making and improved completeness (Parker, 2003;Schouteten & Benders, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of existing studies mainly report negative effects on both working conditions and subsequent health, however, these effects are primarily evident for manual work with low levels of complexity Landsbergis et al, 1999). An and some demonstrate that employees in jobs with higher complexity experienced job improvements such as increased participation in decision making and improved completeness (Parker, 2003;Schouteten & Benders 2004). Therefore, based on the existing contradictory evidence, "an unambiguous negative or causal effect of lean cannot be established" and there is need for a more open and flexible model which accounts for both positive and negative effects (Hasle et al, 2012, p. 845).…”
Section: Introductionmentioning
confidence: 99%